Passive Available Bandwidth Estimation Based on Collision Probability and Node State Synchronization in Wireless Networks - Adhi Rizal; Yoanes Bandung (Journal of ICT Research and Applications, 2017)
In wireless networks, available bandwidth estimation is challenging because wireless channels are used by multiple users or applications concurrently. In this study, we propose a passive measurement scheme to estimate the available bandwidth in 802.12 wireless networks based on the combination and modification of two existing schemes, Distributed Lagrange Interpolation Based Available Bandwidth Estimation (DLI-ABE) and Accurate Passive Bandwidth Estimation (APBE). The proposed scheme uses the channel busy state, which is affected by transmitting or receiving processes caused by carrier sensing. Therefore, the sender and the receiver node should be synchronized using various states that can be affected by other nodes. Moreover, the proposed scheme was developed with the involvement of relevant calculation of possible overhead caused by control messaging that occurs in the Media Access Control (MAC) layer and collision probability caused by data flow from hidden nodes. The result showed that the proposed scheme can estimate the available bandwidth of wireless networks more accurately than DLI-ABE and APBE.